Comparative of the subjective quality of life in the Integral Care Centers of two Spanish-speaking countries: perspective from the aging - Garza Sánchez, Rosa Isabel (2017)
The purpose of the study was to identify the differences in between the perception of the quality of life of the elderly who attend the Instituto de Atención Integral in Saltillo, Mexico and the elderly who attend the Centros Espacio Mayor of the Providencia, municipality in Santiago de Chile, as well as the differences by sex of both samples. We used a quantitative methodology with exploratory scopes. An adapted version of the Quality of Life Questionnaire for Older Adults in Community was used. 535 older adults from Saltillo, Coahuila, Mexico, 49% men (n = 262) and 51% women (n = 273) and 300 older adults from the Municipality of Providencia in Santiago, Chile, were elected by intentional sampling, 11% are men (n = 33) and 89% are women (n = 267). Data were processed by hypothesis testing for independent samples. The results showed that, if there are significant differences in the four sections of the instrument, being relevant the Autonomy section, since the differences were found in the six reagents that make it in favor of the Chilean sample. Regarding the results by sex, significant differences were found in each of the sections.